RANTES release by human adipose tissue in vivo and evidence for depot-specific differences. - Madani, R; Karastergiou, K; Ogston, N; Miheisi, N; Bhome, R; Haloob, N; Tan, G; Karpe, F; Malone-Lee, J; Hashemi, M; Jahangiri, M; Mohamed-Ali, V (2009)
Obesity is associated with elevated inflammatory signals from various adipose tissue depots. This study aimed to evaluate release of regulated on activation, normal T cell expressed and secreted (RANTES) by human adipose tissue in vivo and ex vivo, in reference to monocyte chemoattractant protein-1 (MCP-1) and interleukin-6 (IL-6) release. Arteriovenous differences of RANTES, MCP-1, and IL-6 were studied in vivo across the abdominal subcutaneous adipose tissue in healthy Caucasian subjects with a wide range of adiposity. Systemic levels and ex vivo RANTES release were studied in abdominal subcutaneous, gastric fat pad, and omental adipose tissue from morbidly obese bariatric surgery patients and in thoracic subcutaneous and epicardial adipose tissue from cardiac surgery patients without coronary artery disease. Arteriovenous studies confirmed in vivo RANTES and IL-6 release in adipose tissue of lean and obese subjects and release of MCP-1 in obesity. However, in vivo release of MCP-1 and RANTES, but not IL-6, was lower than circulating levels. Ex vivo release of RANTES was greater from the gastric fat pad compared with omental (P = 0.01) and subcutaneous (P = 0.001) tissue. Epicardial adipose tissue released less RANTES than thoracic subcutaneous adipose tissue in lean (P = 0.04) but not obese subjects. Indexes of obesity correlated with epicardial RANTES but not with systemic RANTES or its release from other depots. In conclusion, RANTES is released by human subcutaneous adipose tissue in vivo and in varying amounts by other depots ex vivo. While it appears unlikely that the adipose organ contributes significantly to circulating levels, local implications of this chemokine deserve further investigation.